Effect of weld angle on the creep rupture life of ferritic/austenitic dissimilar weld interfaces under remote mode I fracture - Hu, J; Elmukashfi, E; Fukahori, T; Igari, T; Chuman, Y; Cocks, A (Elsevier, 2019)
Dissimilar metal welded structures (DMWs) used extensively in conventional and nuclear power plants can suffer from in-service failures at the dissimilar interface with a much reduced life compared to similar metal weld counterparts at the same operating stress and temperature. This paper evaluates the effect of weld angle on the interface creep failure mode of two-dimensional DMW plates consisting of a ferritic steel P91 and an Inconel 82 filler metal within a finite element (FE) framework. A physical cavity growth damage zone model is developed to describe the damage accumulation at the interface, which naturally takes into account the local mode mixity. The material parameters are calibrated against standard 90° weld creep rupture data and used to predict the rupture life of DMWs with a range of axial loads and reduced weld angles (75°, 60°, 45° and 30°). The predicted results match reasonably well with the limited interface failure data for a 45° weld angle. This work also provides additional evidence and insights regarding the improvement of interface creep rupture life of DMWs in power plant pipelines, in particular: (1) Compared with a 45° weld angle, a 60° weld angle is more detrimental to the creep life and should be avoided in actual components – on the contrary, damage tolerance can be promoted by designing and adopting weld angles smaller than 45°, which can have lives exceeding that of standard 90° welded components; (2) A weld interface with alternating weld angles/paths is expected to enable a greater fraction of the creep rupture life to be taken up with crack propagation compared with a flat weld interface, which also increases the probability of damage detection; (3) A fully constrained boundary condition is beneficial to the creep rupture life compared with a free boundary condition; (4) For weld angles less than 90°, the diversion of the crack into the HAZ is less likely compared with a 90° weld angle. Type IV failure mode through the FGHAZ is also less likely to occur.